Unit issues in archaeology : measuring time, space, and material - Ramenofsky, Ann F. (Ann Felice), 1942-; Steffen, Anastasia, 1963- (Foundations of archaeological inquiry., 1998)
The relativity of measurement is one of the paradoxes of science. Even as we seek evidence to explain the world around us, the nature of that knowledge depends on our tools. The apparent inconsistency between what we know and how and what we measure points to the importance of scientific method as a bridge between ideas and entities. This volume emphasizes one aspect of scientific method: units of measure and their construction as applied to archaeology. Attributes, artifact classes, locational designations, temporal periods, sampling universes, culture stages, and geographic regions are all examples of constructed units. Unit Issues in Archaeology discusses how units are defined, described, and evaluated within specified research contexts. Topics include projectile points as chronological markers, the Pecos classification, obsidian and ceramic sourcing, ceramic typology, the "Folsom problem," and landscape-scale units. Throughout the volume, emphasis is placed on the relationship between research goal and measurement. Because research drives the selection and construction of units, units are not treated as unvarying sets of absolutes